Deepening community : finding joy together in chaotic times - Born, Paul (Berrett-Koehler Publishers, Inc., 2014)
Community shapes our identity, quenches our thirst for belonging, and bolsters our physical, mental, emotional, and economic health. But in the chaos of modern life, community ties have become unraveled, leaving many feeling afraid or alone in the crowd, grasping at shallow substitutes for true community. In this thoughtful and moving book, Paul Born describes the four pillars of deep community: sharing our stories, taking the time to enjoy one another, taking care of one another, and working together for a better world. To show the role each of these plays, he shares his own stories--as a child of refugees and as a longtime community activist. It's up to us to create community. Born shows that the opportunity is right in front of us if we have the courage and conviction to pursue it.